If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(7x + -6) = 248 Reorder the terms: -4(-6 + 7x) = 248 (-6 * -4 + 7x * -4) = 248 (24 + -28x) = 248 Solving 24 + -28x = 248 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -28x = 248 + -24 Combine like terms: 24 + -24 = 0 0 + -28x = 248 + -24 -28x = 248 + -24 Combine like terms: 248 + -24 = 224 -28x = 224 Divide each side by '-28'. x = -8 Simplifying x = -8
| 5(5+2x)=9(x-1) | | y-2.52=9.8 | | X-2/y=z | | 2-3x+4+5x=8-(x+2) | | 8-7(n-3)=85 | | 268=8(5-8x)+7x | | -0.001+0.009=0.008 | | 7(-x-8)=-112 | | -1.5x=3 | | y+4.4=8.48 | | 4t-5=6+7t | | -6(x+7)-8=-92 | | -0.2+(0.02)-3=-3.22 | | -4(7x-4)=156 | | 18x+20+x=5+10-3 | | Y^2-4y-14=0 | | y-6.13=8.88 | | 17=3m+8 | | 14x+11x+10=85 | | 5x-(12+2X)=39 | | 0.02x=-18 | | 0.03x=6 | | -6(x-1)= | | 179=15-x | | 30x^3+62x^2-48x=0 | | 30=2(y+6)-5y | | 3(2-3)=5(23-7)+2 | | 7(6+2x)=140 | | 33-2-3=7-3 | | 5x-4=x+24 | | X^2+y^2-6y-247=0 | | -2x+6y=36 |